On the occurrence of the tropical caprellid Paracaprella pusilla Mayer, 1890 (Crustacea: Amphipoda) in Europe - ROS, M.; GUERRA-GARCIA, J.M. (Mediterranean Marine Science, 2012)
Paracaprella pusilla MAYER, 1980 is a tropical caprellid amphipod species first described from Brasil and very common along the Atlantic coast of Central America. Since its original description, P. pusilla has been found at numerous widespread locations in tropical and subtropical seas around the world, primarily associated with fouling communities in harbours. An established population of P. pusilla was recently found in Cádiz, southern Spain, which is both the northernmost collection and first record of this species in European coastal waters. Ship fouling is the most probable vector for its introduction. The species was always found associated with the native hydroid Eudendrium racemosum (CAVOLINI, 1785) and appeared to display a mutualistic relationship with this host.